Choosing HIPS over PRD: It is more than risk reduction. Issue 1 (6th July 2021) - Summers, Angela E.
Abstract: High integrity protective systems (HIPS) are often introduced into the process design package during late‐stage engineering for a new process or integrated with installed equipment in an existing process unit. The decision to use HIPS in addition to, or as an alternative to, a pressure relief device for a particular hazard scenario is generally based on a combination of factors, including technical, regulatory, and capital costs. This paper discusses functional, design, engineering, operation, and maintenance considerations that should be factored into the decision process when choosing HIPS to protect against overpressure scenarios.